The value of urotensin II in patients with left-sided rheumatic valvular regurgitation - Ibrahim Elmadbouh; Mahmoud Ali Soliman; Ahmed Abdallah Mostafa; Haitham Ahmed Heneish (The Egyptian Heart Journal, 2017)
Aims: Rheumatic valve diseases are most common etiological valve diseases in developing countries. Urotensin II is cardiovascular autacoid/hormone and may be associated with patients of heart valve diseases. The present study was to measure plasma urotensin II concentrations in patients with left-sided rheumatic valve diseases such as mitral regurgitation (MR) and aortic regurgitation (AR), and to examine its correlation with severity of valve impairment, function (New York Heart association, NYHA) class and pulmonary artery pressure (PAP). Methods and results: Sixty patients with moderate to severe rheumatic left-sided valve regurgitation and 20 healthy controls were selected after performing the echocardiography. Plasma urotensin II level was measured in all subjects. The patients with MR and AR were significantly increased of left ventricular end diastolic dimension (LVEDD), left ventricular end systolic dimension (LVESD), left atrial diameter, PAP, but decreased of EF% versus the controls. Urotensin II level was highly significant in patients with MR (1.83 ± 0.92 ng/ml, P < 0.001) and AR (0.79 ± 0.3 ng/ml, P < 0.05) versus the controls (0.48 ± 0.13 ng/ml). Also, there was significant correlation between Urotensin II level and LVEDD (MR, r = 0.318, P = 0.03; AR, r = 0.805, P < 0.001), LVESD (MR, r = −0.271, P = 0.115; AR, r = 0.614, P = 0.001), and PAP (MR, r = 0.706, P < 0.001; AR, r = 0.129, P = 0.538). Conclusion: Urotensin II was elevated in patients with rheumatic left-sided valvular regurgitation, and positively correlated with increased LVEDD (in both MR and AR), LVESD (only AR) and pulmonary artery pressure (only MR). Therefore, urotensin II level may be used as diagnostic biomarker in patients with rheumatic valvular diseases for assessment of the severity in parallel with echocardiography.